WE ARE [TRULY] DIFFERENT: OTHERING IN INTER-ETNIC RELATION IN ROYYAN JULIAN’S SHORT STORY - Hartanto, Erika Citra Sari; Inayati, Rif’ah (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
Royyan Julian’s short story entitled “Di Malam Bulan Darah, Mogut Menyantap Jenazah Orang Kafir” [On the Night of the Blood Moon, Mogut Eats the Body of Infidel] (2019) captures the relationship among different ethnic groups, religions and gender in Madura. Set in Madura Island, the story uncovers more than just relation between Chinese and Madurese people and between female and male characters. This paper is focusing on inter-ethnic and inter-religion relation in the short story. This analysis used qualitative method and data collection used close-reading. Drawing theoretical inspiration from Simone de Beauvoir with a particular emphasis on the Other and Richard Jenkins’ theory on Social Identity, this study reveals how different identities bring different treatment, evaluation, and prejudice which led to othering. Through his short story, Royyan Julian discloses binary opposition related to ethnicities, religions, and gender. The hierarchy and power imbalance imposed on male and female characters in the story bring devastated impact on female character just because she has different identity from the majority of Muslims in Madura.